The Effects of Facial Adiposity on Attractiveness and Perceived Leadership Ability. Issue 4 (April 2014) - Re, Daniel E.; Perrett, David I.
Facial attractiveness has a positive influence on electoral success both in experimental paradigms and in the real world. One parameter that influences facial attractiveness and social judgements is facial adiposity (a facial correlate to body mass index, BMI). Overweight people have high facial adiposity and are perceived to be less attractive and lower in leadership ability. Here, we used an interactive design in order to assess whether the most attractive level of facial adiposity is also perceived as most leader-like. We found that participants reduced facial adiposity more to maximize attractiveness than to maximize perceived leadership ability. These results indicate that facial appearance impacts leadership judgements beyond the effects of attractiveness. We suggest that the disparity between optimal facial adiposity in attractiveness and leadership judgements stems from social trends that have produced thin ideals for attractiveness, while leadership judgements are associated with perception of physical dominance.